Modeling of Flow Stress of 2026 Al Alloy under Hot Compression - Zheng-bing Xiao; Yuan-chun Huang; Yu Liu (Advances in Materials Science and Engineering)
In order to investigate the workability and to optimize the hot forming parameters for 2026 Al alloy, hot compression tests were performed in the temperature range of 350~450°C with strain rates of 0.01~10 s−1 and 60% deformation degree on a Gleeble-1500 thermosimulation machine. The true stress-strain curves obtained exhibit that the stress increases dramatically at small strains and then moves forward to a steady state, showing dynamic flow softening. Meanwhile, on the basis of Arrhenius equation, a constitutive equation on the flow stress, temperature, and strain rate was proposed. Yet, the values of the predicated stress from the equation and the true stress differ by as much as 50.10%. Given the intricate impact of precipitation of the second phases on the strength of 2026 Al alloy, the introduction of a revised equation with the reinforcement of temperature was carried out, fitting well with the experiment data at peak stresses. What is more, both pictures obtained by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were compatible with all the inferences.